Introduction to relativistic continuum mechanics - Ferrarese, Giorgio (Springer-Verlag Berlin and Heidelberg GmbH and Co. KG, 2017)
This mathematically-oriented introduction takes the point of view that students should become familiar, at an early stage, with the physics of relativistic continua and thermodynamics within the framework of special relativity. Therefore, in addition to standard textbook topics such as relativistic kinematics and vacuum electrodynamics, the reader will be thoroughly introduced to relativistic continuum and fluid mechanics. There is emphasis on the 3+1 splitting technique.